Evaluation of different teaching methodologies by assessing the performance of dentistry students - Guirado, Milena Miranda Goulart [UNESP]; Tango, Rubens Nisie [UNESP]; Silva, Vanessa Ramos da [UNESP]; Bardini, Vivian Silveira Dos Santos; Spalding, Marianne [UNESP]; Rodgher, Suzelei [UNESP] (Editora Cubo, 2023)
Objective: The aim of this study was to compare the performance of day-and evening-class students in the first semester test of Dental Materials in the School of Dentistry at São José dos Campos-UNESP, who were exposed to traditional lectures (TRAD) and Team-Based Learning (TBL). Material and Methods: The results of Dental Materials first semester test of students, from day and evening classes of 2016 were tabulated and analyzed in this research. The groups formed for the execution of the methodology were randomized using the individual global average of the previous year of the students, and the groups were composed of 6 to 7 members, maintained throughout the course. During the correction of the tests, the subject of each question and the applied methodology (TBL and TRAD) were identified. Responses of each question were graded separately according to the subject for comparison between methodologies. A total of 88 tests were evaluated. The performance was evaluated through a comparison of the average grade of each question, related to a specific learning methodology. The data were submitted to t-test. Results: The students’ overall performance was similar when both methodologies were compared. Students from day class presented higher grades with TBL whilst evening class students presented better performance in questions with traditional lectures. Conclusion: Active learning should be further implemented in Brazilian Dental Schools to change students’ habits aiming to improve their personal and social skills besides of professional technical knowledge.
Avaliação de diferentes metodologias de aprendizagem aferindo o desempenho de estudantes de odontologia
Keywords: Dental Schools; Educational activities; Higher education; Learning; Student evaluation